Corticosteroid use in ARDS and its application to evolving therapeutics for coronavirus disease 2019 (COVID‐19): A systematic review. Issue 1 (28th October 2021) - Landolf, Kaitlin M.; Lemieux, Steven M.; Rose, Christina; Johnston, Jackie P.; Adams, Christopher D.; Altshuler, Jerry; Berger, Karen; Dixit, Deepali; Effendi, Muhammad K.; Heavner, Mojdeh S.; Lemieux, Diana; Littlefield, Audrey J.; et al.
Abstract: Data regarding the use of corticosteroids for treatment of acute respiratory distress syndrome (ARDS) are conflicting. As the coronavirus disease 2019 (COVID‐19) pandemic progresses, more literature supporting the use of corticosteroids for COVID‐19 and non‐COVID‐19 ARDS have emerged. Glucocorticoids are proposed to attenuate the inflammatory response and prevent progression to the fibroproliferative phase of ARDS through their multiple mechanisms and anti‐inflammatory properties. The purpose of this systematic review was to comprehensively evaluate the literature surrounding corticosteroid use in ARDS (non‐COVID‐19 and COVID‐19) in addition to a narrative review of clinical considerations of corticosteroid use in these patient populations. OVID Medline and EMBASE were searched. Randomized controlled trials evaluating the use of corticosteroids for COVID‐19 and non‐COVID‐19 ARDS in adult patients on mortality outcomes were included. Risk of bias was assessed with the Risk of Bias 2.0 tool. There were 388 studies identified, 15 of which met the inclusion criteria that included a total of 8877 patients. The studies included in our review reported a mortality benefit in 6/15 (40%) studies with benefit being seen at varying time points of mortality follow‐up (ICU survival, hospital, and 28 and 60 days) in the COVID‐19 and non‐COVID‐19 ARDS studies. The two non‐COVID19 trials assessing lung injury score improvements found that corticosteroids led to significant improvements with corticosteroid use. The number of mechanical ventilation‐free days significantly were found to be increased with the use of corticosteroids in all four studies that assessed this outcome. Corticosteroids are associated with improvements in mortality and ventilator‐free days in critically ill patients with both COVID‐19 and non‐COVID‐19 ARDS, and evidence suggests their use should be encouraged in these settings. However, due to substantial differences in the corticosteroid regimens utilized in these trials, questions still remain regarding the optimal corticosteroid agent, dose, and duration in patients with ARDS.